National security review of foreign investments in Hungary - Károly László Simon; Katalin Gombos (DANUBE: Law, Economics and Social Issues Review, 2021)
Screening mechanisms as investment policy measures keep gaining importance worldwide.In October 2018, the Hungarian Parliament also adopted rules on the national securityreview of foreign investments. This paper intends to present the newly introducedHungarian screening mechanism which is applicable from 1st January 2019. The goalof this article is to determine how the established Hungarian FDI system can be typified,integrated into an existing regulatory model, or whether it carries elements of a multi-layered system, possibly providing a completely new approach to FDI. We concludethat Hungarian new rules on foreign investment control have become more transparentand coherent than in the past. Nonetheless the review process suffers from a numberof shortcomings that may hinder the full accomplishment of the predictability and theeffectiveness.
Keywords: 330; Foreign Investment; Investment Screening; National Security Review; Hungary